Moral Values in Interstellar Movie: A Father-Daughter Relationship - Rahmah, Salwa Sabita (Saree: Research in Gender Studies, 2024)
ABSTRACT ENGLISH:This study investigates the moral values embedded in Christopher Nolan's film Interstellar, with the goal of identifying and analysing the ethical lessons conveyed by its narrative. The research employs a qualitative methodology, with an in-depth examination of key scenes that depict moral values. The study identifies eight key moral values in the film: honesty, bravery, protection, discipline, love and affection, kindness and friendliness, loyalty, and the complex father-daughter relationship. Each value is critically evaluated within the context of the storyline, emphasizing its impact on the characters' decisions and the film's overall message. To uncover and interpret the moral values embedded in specific scenes of Interstellar, the researcher used Linda and Eyre's (1993) theoretical framework from "Teaching Your Children Values". The findings show that Interstellar goes beyond its role as a source of entertainment to serve as a powerful medium for imparting moral lessons. By addressing universal themes such as human connection, responsibility, and ethical quandaries, the film establishes itself as a valuable moral education resource, providing insights that will resonate deeply with a wide range of audiences. ABSTRACT INDONESIAN:Tujuan penelitian ini adalah untuk menemukan dan menganalisis pelajaran moral yang disampaikan oleh tokoh-tokoh dalam film Interstellar oleh Christopher Nolan. Penelitian ini menggunakan metodologi kualitatif, melakukan pemeriksaan mendalam terhadap bagian penting dari nilai moral. Menurut penelitian ini, ada delapan prinsip moral utama yang terkandung dalam film: kejujuran, keberanian, perlindungan, disiplin, cinta dan kasih sayang, kebaikan dan keramahan, kesetiaan, dan hubungan ayah-anak yang kompleks. Nilai-nilai diperiksa secara menyeluruh sesuai dengan alur cerita, dengan penekanan pada pengaruh mereka terhadap keputusan yang dibuat oleh karakter dan pesan film secara keseluruhan. Peneliti menggunakan kerangka teori Linda dan Eyre (1993) dari "Teaching Your Children Values" untuk mengungkap dan menginterpretasikan nilai moral yang terkandung dalam adegan tertentu dalam film Interstellar. Hasil penelitian ini menunjukkan bahwa Interstellar tidak hanya sebagai berperan sebagai media hiburan, namun menjadi medium yang efektif untuk memberikan nilai-nilai moral. Film ini berperan sebagai sumber pendidikan moral yang berharga dengan mengangkat tema-tema seperti pelajaran etika, hubungan antar manusia, dan tanggung jawab. Selain itu, film ini juga memberikan wawasan yang akan beresonansi secara mendalam bagi penonton.